Leaf anatomical characters variation of Strobilanthes s.l. from Sumatra, Indonesia and its taxonomic implications - SURATMAN SURATMAN; SURANTO SURANTO; MUZZAZINAH MUZZAZINAH; PURNOMO PURNOMO (Society for Indonesian Biodiversity, 2022)
Abstract. Suratman, Suranto, Muzzazinah, Purnomo. 2022. Leaf anatomical characters variation of Strobilanthes s.l. from Sumatra, Indonesia and its taxonomic implications. Biodiversitas 23: 3705-3720. The objective of this study was to evaluate leaf anatomical character variation among species of Strobilanthes s.l. from Sumatra. A total of 35 species from four genera previously recognized within the subtribe Strobilanthineae (Strobilanthes, Hemigraphis, Sericocalyx, Semnostachya) were used for leaf paradermal section observations. A total of seventeen leaf anatomical characters consisting of ten quantitative and seven qualitative characters were selected for leaf anatomical comparison. The quantitative and qualitative character analysis showed great variability in the majority of tested leaf anatomical characters. This result indicates the large diversity of leaf anatomical characters occurs among species of Strobilanthes s.l. A similarity dendrogram among species of Strobilanthes s.l. based leaf anatomical character data revealed two major clusters. The first cluster consists of eleven species with regular epidermal cell shape and straight cell wall with a similarity coefficient of 0.67. The second cluster consists of twenty four species that differed from species in the first cluster due to their irregular epidermal cell shape and undulate anticlinal cell wall with a similarity coefficient of 0.59. This study indicates that leaf anatomical characters are valuable taxonomic features in taxa delimitation at the species level. The results of this study also support earlier works through molecular studies that all members of the Strobilanthinae then accepted as Strobilanthes s.l. group which could not be easily split into smaller component genera.